Coronavirus pandemic and canon law. Selected aspects in divine worship - Domaszk, Arkadiusz (Prawo Kanoniczne, 2024)
The situation of the coronavirus pandemic has caused many social impacts. At the same time, the Church in Poland demonstrated a number of adaptive practices, i.e., that the Church community is able to proclaim the Gospel of Jesus Christ under all conditions and enjoy the beauty of liturgical life, even under unfavorable circumstances. Impediments to the enjoyment of the Eucharist triggered dispensations, granted by diocesan bishops. The spiritual needs of the faithful were met, as it were, by numerous television, radio and Internet transmissions of the Mass. And in the sacred space, church communities became accustomed to the use of disinfectants. A lasting remnant of the time of the pandemic is, among other things, the form of administering Holy Communion, equivalently on the hand and into the mouth. After the pandemic ceased, the celebration of the sacraments and sacramentals returned, as it were, to their usual rhythm. The experience of the past should be used looking toward the future. A number of different ecclesiastical dispositions, issued at different levels of governance, in relation to the time of the pandemic, prompt the following reflection. Humanity cannot predict when the next pandemic will occur. However, the preparation of general Church guidelines (e.g., in the form of a directorium) can be postulated. A possible Church-wide document should address norms and guidelines for pastoral care and liturgical principles in the face of extraordinary pandemic circumstances. Such a document could include norms to be applied at the level of the Conference of Bishops, bishops and even individual ministers, taking into account canonical justice in specific situations . Post-pandemic legal and canonical reflection covers a number of areas, such as preaching and education. Another space of reflection is the issue of the celebration of the liturgy of the Catholic Church. The author of this study is aware that many detailed questions about the liturgy during the pandemic still need to be deepened, and the considerations made have necessarily not covered all aspects. The effects of the pandemic require further study, for example, in the area of religious freedom and state-church relations, if only because the decisions of state authorities in many cases imposed solutions that did not fully protect the rights of the faithful. Another space for future reflection is the question of the exercise of ecclesiastical authority and administration in emergency situations and the creation of legal and canonical acts. The Catholic Church is putting its trust in God, Who guides His Church through various events in human history. Also, when these are such difficult episodes as epidemics and pandemics. And at the same time, the events of the pandemic time have shown that the Church's structures and faithful are able to fulfill their mission in creative ways.